Optimalisasasi Pembelajaran Agama Hindu Berbasis Aplikasi Online Bagi Siswa Hindu di SMAN 1 Basarang Kabupaten Kapuas - I Gede Dharman Gunawan; Ni Wayan Gateri (Jayapangus Press, 2022)
The existence of distance learning also demands creativity and innovation of Hindu religious education teachers in managing Hindu religious education learning through online learning applications. The online learning system that is commonly implemented is the teacher using the Whats App (WA) application because it is considered easy and commonly used by students. The teacher creates a class group and then sends materials and assignments through the group. However, it turns out that this is not optimal for the implementation of Hindu religious learning, so it is necessary to optimize Hindu religious education learning by utilizing online learning applications for Hindu students at SMAN 1 Basarang, Kapuas Regency. The purpose of this study was to find out how the process of learning Hindu religion based on online applications at SMAN 1 Basarang, Kapuas Regency. The results of this study include the online application-based Hindu religious learning process at SMAN 1 Basarang, Kapuas Regency, the preparation, implementation, and evaluation of online application-based Hindu learning at SMAN 1 Basarang and efforts to optimize online application-based Hinduism learning at SMAN 1 Basarang from the headmaster's efforts. schools, efforts of Hindu religious education teachers, efforts of educational staff, and student efforts.